Perbandingan hasil belajar siswa sebelum dan sesudah penggunaan LKS IPA terpadu bermuatan literasi saintifik tema kesehatan pencernaan kelas VIII SMPN 17 Padang - Rima Surwanti; yurnetti yurnetti (Universitas Negeri Padang, 2019)
The 2013 curriculum requires the science learning carried out in an integrated pattern. In addition, the scientific literacy need to be integrated into science learning. But the real condition indicated that integrated science learning can be implemented according the 2013 curriculum.. One solution to this problem is to use an integrated science student worksheet by integrating the scientific literacy. The purpose of this research was to compare the learning outcomes of students between before and after the use of the integrated science student worksheets by integrating the scientific literacy on the theme of digestive health in grade VIII of SMPN 17 Padang. The type of the research was quasi experimental research with a before-after design. The research population was all eighth grade students of SMPN 17 Padang academic year 2018/2019. The sample of this research was a grade VIII which was determined by using both purposive sampling and cluster random sampling techniques. The research instruments were consisted of observation sheets attitudes aspect of attitude, written tests in the form of multiple choices for knowledge aspec knowlegde, and performance assessment sheet of skills aspect. Data from research results were analyzed by descriptive statistical analysis and correlation comparison test. Based on the results of data analysis, it can be stated that there are significant differences in student learning outcomes before and after the use of the integrated science student worksheets by integrating the scientific literacy on the theme digestive health of grade VIII students in SMPN 17 Padang with a confidence level of 95 %. It means that the use of integrated science student worksheet by integrating the scientific literacy on the theme of digestive health has given a significant effect on the student learning outcomes which includes aspects of attitudes, knowledge and skills. Thus, the integrated science student worksheet which implemented in scientific approach can be used as an alternative solution to problem of integrated learning in the schools.